DEVELOPMENT OF THE PAPPASENG TO RIOLO SOCIODRAMA MODEL TO ENHANCE THE ACHIEVEMENT MOTIVATION OF 11TH-GRADE STUDENTS AT SMK NEGERI 2 PANGKEP - Nur Mila Sari; Abdullah Pandang; Suciani Latief (Jurnal Konseling Pendidikan Islam, 2026)
Achievement motivation is an important factor determining students' success in the learning process. Initial findings in class XI Light Vehicle Body Engineering (TBKR) at SMK Negeri 2 Pangkep show that some students have low achievement motivation, characterized by passive behavior, lack of academic responsibility, and minimal effort to achieve optimal learning outcomes. This research aims to develop a sociodrama group guidance model based on Pappaseng to Riolo as an effort to increase students' achievement motivation. The research method used is Research and Development (R&D) by adapting a development model that includes needs analysis, prototype preparation, expert validation, and practicality testing. The values of local wisdom in Bugis Pappaseng to Riolo, especially the principle of resopa temmangingngi namalomo naletei pammase dewata, are integrated into the sociodrama scenario to foster hard work, responsibility, and perseverance. The results show that the developed model is in the very valid category based on expert assessment, and is considered practical to be applied in group guidance services in schools. Thus, the Pappaseng to Riolo-based sociodrama model is effective as an alternative guidance and counseling service to increase vocational students' achievement motivation.